Aggression and Violence Toward Healthcare Workers in a Psychiatric Service in Italy: A Retrospective Questionnaire-Based Survey. Issue 4 (April 2020) - Bizzarri, Jacopo V.; Piacentino, Daria; Kotzalidis, Georgios D.; Moser, Sabine; Cappelletti, Simone; Weissenberger, Gerd; Pompili, Maurizio; Conca, Andreas
Abstract : Abstract: Workplace violence and aggression are receiving increasing attention, especially when perpetrated in at-risk services such as psychiatric and emergency departments. Many healthcare providers have been victims of verbal aggressions (VAs) and physical aggressions (PAs), as well as injuries (INs), at the hands of patients. We conducted a 1-year retrospective questionnaire-based survey to assess workplace violence and aggression experienced by staff working at the Psychiatric Service of the Health District of Bolzano-Bozen (Italy). We performed parametric statistics. Logistic regression estimated the size of the association between PA occurrence and staff characteristics. Our psychiatric service's employees were frequent victims (91.5%) of 1 or more aggression/injury in the previous year. VAs and INs showed comparable frequencies among the three sites of our service, that is, the inpatient (INP), the outpatient (OUTP), and the rehabilitation (REHAB) units, differently from PAs, which were more common at INP ( p < 0.001). The logistic regression model showed that female sex, working at INP, and a shorter psychiatry work experience predicted PAs occurrence. Most of the staff felt they could benefit from aggression management. Findings show that VAs, PAs, and INs are common among our psychiatric service's employees and point to the need to provide staff training on de-escalation.